2021
DOI: 10.1111/mcn.13169
|View full text |Cite|
|
Sign up to set email alerts
|

Grandparent caregiving in Cambodian skip‐generation households: Roles and impact on child nutrition

Abstract: This study aims to understand nutrition‐related roles, responsibilities and ethical issues of grandparents caring for their grandchildren in skip‐generation households in rural Cambodia. Over the past decade, Cambodia has experienced a rise in economic migration of working age populations. This has resulted in increasing numbers of ‘skip‐generation’ households, in which grandparents and grandchildren co‐reside without parents, reflecting potential household vulnerability. This qualitative study involved in‐dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…These contextual factors may have contributed to the modest improvements in child nutritional status at the 12-mo follow-up ( 20 ). Our findings align with another study by Schneiders et al ( 24 ), which observed that, in migrant households, grandparents are the primary caregivers for children and tend to their nutritional needs. The study also highlighted that to improve child nutrition, interventions need to be designed in ways to support and enable grandparent caregivers in Cambodia.…”
Section: Discussionsupporting
confidence: 93%
“…These contextual factors may have contributed to the modest improvements in child nutritional status at the 12-mo follow-up ( 20 ). Our findings align with another study by Schneiders et al ( 24 ), which observed that, in migrant households, grandparents are the primary caregivers for children and tend to their nutritional needs. The study also highlighted that to improve child nutrition, interventions need to be designed in ways to support and enable grandparent caregivers in Cambodia.…”
Section: Discussionsupporting
confidence: 93%
“…These negative associations may be attributed to limitations in grandparental care practices as noted in the literature, such as ineffective discipline and low nurturance (Smith, Cichy, & Montoro‐Rodriguez, 2015), a possible result of grandparents' energy and health limitations and their psychological distress (Smith & Hancock, 2010). Some studies also suggest that grandparents of left‐behind children (whose parents had migrated for work purpose) may lack the knowledge and awareness about the importance of stimulating child development (Schneiders et al., 2021; Urrieta & Martínez, 2011). Furthermore, as grandparents age and no longer have a spouse to share the caretaking responsibilities, they can be physically and emotionally overwhelmed, which may further compromise grandparenting outcomes (Chan et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, assuming the caregiving role is generally not expected from men, male caregivers are more likely to be acknowledged or appreciated than female caregivers, whose efforts are expected and usually unnoticed (Bullock, 2005). Higher depressive symptoms among grandmothers may also be due to different ARC duties taken by grandmothers in contrast to grandfathers; whereas grandmothers take more responsibility for tasks including cooking, feeding, cleaning, doing laundry, and providing basic care to grandchildren, grandfathers could be responsible for peripheral care roles, like taking grandchildren to school or entertaining them (Schneiders et al, 2021). These differences can create both actual load and higher perceptions of subjective stress among grandmothers resulting from their demanding care tasks.…”
Section: Discussionmentioning
confidence: 99%